ESP Needs-Based Course Design for the Employees of Government Protocol Department - Badriyah Ulfah; Ismail Petrus; Soni Mirizon (English Language in Focus (ELIF), 2021)
Needs analysis plays an important role in the context of designing the ESP course. Hutchinson and Waters (1989) classify needs into two main categories: learning and target. Learning needs refer to what the student needs to do to learn; target needs include necessities, wants, and lacks. To collect data for those two fundamental aspects of needs, various forms of analysis were used, i.e Target Situation Analysis (TSA), Present Situation Analysis (PSA), Learning Strategy Analysis (LSA), deficiency analysis, and Means Analysis (MA). This article represents the process of designing an ESP course design for the employees of the Protocol Department in the Palembang City Mayor Office, which focuses on the needs analysis gathered through questionnaires, interviews, and observations. The data were analyzed both quantitatively and qualitatively. The results of the needs analysis were used to provide employees with a course design.  The proposed course is designated as English for Professional Purposes: Basic level of conversation.